Study of Perceived Accessibility in Daily Travel within the Metropolis - Anastasia Vladimirovna Lukina; Roman Roaldovich Sidorchuk; Sergey Vladimirovich Mkhitaryan; Anastasia Alexeevna Stukalova; Irina Ivanovna Skorobogatykh (Ital Publication, 2021)
The growth of metropolises and the number of vehicles cruising within their boundaries creates a permanent problem of dissatisfaction with transport accessibility. This study aims to identify the difference between perceived (PA) and objective (OA) transport accessibility. For its implementation, it was necessary: to explore PA between different residential areas and travel modes, reveal the influence of the travel regime on the PA, compare the impact of social-demographic factors on the individuals' PA. The research methodology is based on a large cross-sectional study with 2,275 respondents. A quota sample was used for 12 administrative districts of the Moscow metropolis. The data was processed by IBM SPSS Statistics 20 statistical program to obtain descriptive statistics indicators. Correlation analysis of the respondent's answers to the four items for PA assessment was performed to assess the relationship between the results of the solutions. Next, a synthetic index of PA was calculated and analyzed differences using the integral index PA. The relationship significance was assessed using F-criterion-based one-way ANOVA. The novelty of our study is as follows: it contributes to previous research on the possibility of measuring perceived affordability in metropolitan areas and benchmarking OA and RA. Doi: 10.28991/esj-2021-01316 Full Text: PDF